EVALUATION OF ANTAGONIST ACTIVITY OF IFENPRODIL AND THEIR ANALOGOUS AGAINST GLUN1/GLUN2B USING IN SILICO MOLECULAR DOCKING AND ABSORPTION-DISTRIBUTIONMETABOLISM- EXCRETION TOXICITY - PRAVEEN, MALLARI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: High Ca2+ permeability represents a characteristic feature of N-methyl-D-aspartate (NMDA) receptors that in extreme amounts affects physiological functions such as reduced neural development, synaptic plasticity, and learning and memory. The study aims to elucidate the potent inhibitory ifenprodil and their eleven analogues, retrieved from the PubChem database, which act as ligands to the target Glun1/GluN2B subunit of the NMDA receptor. Methods: In silico methods such as molecular docking performed using AutoDock Vina and absorption-distribution-metabolism-excretion-toxicity (ADMET) were SwissADME and OSIRIS carried out to elucidate the potent antagonist ligand against the target. Results: Molecular docking showed that six of the compounds had significant binding affinities (7.8–9.0 kcal/mol) for the target. The ADMET study revealed that three (PubChemID: 12613159, 12613162, and 6604117) of six compounds with good binding affinity obeyed Lipinski’s rule of five. Conclusion: This study revealed three good antagonists of GluN1/GluN2B, namely, 4- [(1R, 2R)-2-(4-benzylpiperidin-1-yl)-1- hydroxy propyl] phenol (A2), 4-[2-(4-benzylpiperidin-1-yl)-1-hydrooxypropyl] phenol hydrobromide (A4), and 4- [(1R, 2S)-2-(4-benzylpiperidin-1-yl)-1-hydroxypropyl] phenol (A7) that can be further exploited for wet lab studies.